Effect of Content Marketing, Price Discount, and Social Influence On Purchase Decision Through Purchase Intention: A Study on the Instagram Followers of Beauty Store Mitufaya in Malang - Shiddiqy, Isymayati Ash; Pratikto, Heri (JURNAL MANAJEMEN MOTIVASI, 2025)
This  study  analyzes  the  influence  of  content  marketing,  price discounts, and social influence on purchase decisions, mediated by purchase intention. The research targets Instagram followers of the Mitufaya beauty store in Malang, Indonesia, using a descriptive and explanatory  quantitative  approach.  A  total  of  186  followers  were selected  as  the  sample.  Data  were  analyzed  using  Structural Equation  Modeling  (SEM)  via  SmartPLS.  Results  show  that content  marketing  and  price  discounts  significantly  affect  both purchase  intention  and  decision.  Social  influence  significantly affects  purchase  intention  but  not  purchase  decision.  Purchase intention  significantly  mediates  the  effects  of  all  independent variables on purchase decisions.